2017
DOI: 10.2514/1.j055597
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and Entropy Waves in Nozzles in Combustion Noise Framework

Abstract: A low-order model is presented to study the propagation and interaction of acoustic and entropic perturbations through a convergent-divergent nozzle. The calculations deal with choked, unchoked, as well as compact and non-compact nozzles. In the choked case, a normal shock exists in the divergent section of the nozzle. To validate the models developed, cylindrical configurations corresponding to Entropy-WaveGenerator (EWG) and Hot-Acoustic-Testrig (HAT) of DLR are studied. For the EWG, an entropy wave is gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
(71 reference statements)
1
7
0
Order By: Relevance
“…Excellent agreement is observed between the 2D model and CAA results for all the forcings considered and the compact solution of Marble & Candel [19] is correctly recovered by the model as well. With entropy forcing, 2D transfer functions collapse well with the quasi-1D solution classically used in the literature [28,29,[31][32][33] in the low frequency range but discrepancies increase as frequency rises because the radial distortion of the entropy wave is not taken into account by the quasi-1D approach. Of interest, quasi-1D modelled transfer functions collapse with CAA data in the case of acoustic forcings, which indicates that 2D mean flow effects are negligible for noise scattering through the nozzle.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Excellent agreement is observed between the 2D model and CAA results for all the forcings considered and the compact solution of Marble & Candel [19] is correctly recovered by the model as well. With entropy forcing, 2D transfer functions collapse well with the quasi-1D solution classically used in the literature [28,29,[31][32][33] in the low frequency range but discrepancies increase as frequency rises because the radial distortion of the entropy wave is not taken into account by the quasi-1D approach. Of interest, quasi-1D modelled transfer functions collapse with CAA data in the case of acoustic forcings, which indicates that 2D mean flow effects are negligible for noise scattering through the nozzle.…”
Section: Discussionsupporting
confidence: 60%
“…This approach proved efficient to design a nozzle with optimal indirect noise generation through the use of a genetic algorithm, for instance [30]. In a different way, Mahmoudi et al [31] discretised the nozzle as a succession of ducts of constant radii and used the compact solutions to link acoustic, entropy and vorticity waves (including azimuthal modes) between successive elements.…”
mentioning
confidence: 99%
“…It is suggested that the impact of perturbations in the mixture composition is important for advanced low-emission combustors with supersonic flows, and can reach amplitudes comparable to the direct noise and entropy noise [7]. Without considering the contribution of noise due to the mixture composition, the entropy noise is believed to be the main mechanism of noise generation downstream of the combustion chamber [8]. It also has been shown that, without considering entropy wave attenuation in the turbine stage, engine noise is over predicted by almost two orders of magnitude [9].…”
Section: Introductionmentioning
confidence: 99%
“…The indirect noise, however, is emanated from the convecting disturbances of temperature, chemical composition, or vorticity passing through a region of strong pressure gradient and thus flow acceleration [7,8]. Such disturbances are generated by the flame while their conversion to sound occurs in the combustor exit nozzle and the first stage of the turbine blade [9,10]. It follows that the occurrence of indirect combustion noise depends upon the survival of convecting disturbances throughout their journey from the flame to the downstream nozzles.…”
Section: Introductionmentioning
confidence: 99%